Processos de subjetivação, governamentalidade neoliberal e resistência: uma leitura a partir de Michel Foucault e Judith Butler - Marinho, Cristiane Maria (2020)
This research aims at presenting the analytic of power and the notion of resistence in Michel Foucault's thinking, as well as to explain the way in which Judith Butler talks over these concepts and develops them in an original and updated reading of the contemporary neoliberal governmentality. The thesis defended here, was that, to those two philosophers, exists a crucial importance in the subjectivation process, both in the exercise of power of neoliberal governanmentability as for the formation of resistence against this governementality in particular, and in the ethical-political-economic contemporaneity of the twentieth and twenty-first centuries. Firstly, it  has been presented here Foulcadian analytic of  power, highlighting the same subjectivation processes in the exercise of the mechanisms of modern and contemporary power and in Butler's proposition about the need for developing a new analytic  of power,  updating Foucault's writings, but starting off from the new movements of contemporary  power  and describing the upsurge of sovereignty within governamentality. And then, it has been further developed the notion of neoliberal governmentality, typifying the German and American neoliberalism and, following foucaultian's analysis, it has been proved that the neoliberalism is, more than just an economic paradigm, a liberal rationality, being the process of subjetivation a critical category in the exercise of power. There has also been presented Butler's dialogue with these foucauldian issues with regard to the "assujettissement" in which criticizes Foucault for disregarding some subvertion potential within the psyche in the analysis of power and in the formation of resistence to the exercise of governmentality. Finally, it has been addressed the possibilities of resistence to the power of neoliberal governmentality in Foucault and Butler and their agonistic clash, in addition to a short genealogy of the notion of resistence in  Foulcault's  work, exploiting the importance of the processes of subjectivation in the exercise of the governmental power as well as in the  exercise of resistence to mechanisms of power starting off with the practices of freedom, of aesthetics of existence as well as the Criticism, taking into account the notions of "parresía" and counter-conduct. It has also been presented that Butler, inspired by Foucault, thinks about  the centrality of processes of subjectvation in the resistence to the neoliberal governmentality, starting off from foucaudian criticism as virtue; of performative politics; of neoliberal precariety; of alliance of the diversities  in search of recognition; of the post-identity interdependence, but without refusal of identities.